Potential geographic distributions of two parthenogenetic weevils (Coleoptera: Curculionidae) associated with citrus in Argentina and Brazil - Río, María Guadalupe del (2019)
Parapantomorus fluctuosus (Boheman) and Pantomorus cinerosus (Boheman) (both Coleoptera: Curculionidae) are parthenogenetic broad-nosed weevils native to South America, and they damage citrus in Argentina and Brazil. The objectives of this contribution are to apply ecological niche modelling to compare the suitable areas of occurrence of these species with those of other parthenogenetic Naupactini distributed in similar areas, and to analyze their potential range in relation to the distribution of citrus groves, mainly in Argentina and Brazil. Pantomorus cinerosus and P. fluctuosus were predicted to be distributed in tropical and subtropical South America, Mexico, Central America, Cuba, southeastern USA (Florida), southern Africa, Madagascar, eastern Australia, and southern China. However, neither has colonized other countries outside the native range. The potential distribution of P. fluctuosus is broader than that of P. cinerosus, and the predicted areas of both species are partially coincident with main production areas of citrus in Argentina, Brazil, and throughout the world. Although ecological niche modelling is an effective tool for predicting the potential spread and colonization of weevils in distant cultivated areas, weevil establishment is most likely the result of multiple factors.